High-achieving high school students’ strategies for writing from Internet-based sources of information - Kirkpatrick, Lori C.; Klein, Perry D. (Journal of Writing Research, 2016)
This study investigates Grade 12 students’ global and local strategies for writing from the Internet. Analysis of screen captures, think-aloud protocols, and interviews showed two global writing strategies: 1) Students created mediating planning documents; they alternated between researching online and creating mediating planning documents, then drafted a text, and then revised. 2) Students created no (or almost no) mediating documents; they wrote directly from the source documents, alternating frequently between researching, drafting, and revising. Each global strategy comprised several sub-ordinate strategies (e.g., search using a combination of content and rhetorical keywords; take hard copy notes; draft a text out of the sequence in which it appears in the final text; use automatic spelling and grammar checkers to guide review). Some of these strategies are similar to those used in print-based writing from sources. However, using the Internet also resulted in new researching and writing strategies. We argue that writers created task environments and used strategies that maximized the affordances of the Internet, electronic writing medium, and internal cognition, and minimized their constraints. This work extends classical cognitive work on writing as well as more recent work on writing from sources.